2017
DOI: 10.1617/s11527-017-1115-6
|View full text |Cite
|
Sign up to set email alerts
|

Bond of steel reinforcement with microwave cured concrete repair mortars

Abstract: This paper investigates the effect of microwave curing on the bond strength of steel reinforcement in concrete repair. Pull-out tests on plain mild steel reinforcement bars embedded in four repair materials in 100 mm cube specimens were performed to determine the interfacial bond strength. The porosity and pore structure of the matrix at the steel interface, which influence the bond strength, were also determined. Test results show that microwave curing significantly reduces the bond strength of plain steel re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…This research investigation reports the relationship between test results of internal and surface temperatures monitored on specimens of concrete repair mortars. The authors have previously reported on the parameters of microwave curing which affect the strength and other properties of concrete repair materials [20] including bond between a repair patch and both the substrate concrete and the steel reinforcement [21,22]. However, the interaction between microwave curing and hydration temperatures at early age can have significant effect on the properties and long term deterioration processes in concrete repair patches [23].…”
Section: Introductionmentioning
confidence: 99%
“…This research investigation reports the relationship between test results of internal and surface temperatures monitored on specimens of concrete repair mortars. The authors have previously reported on the parameters of microwave curing which affect the strength and other properties of concrete repair materials [20] including bond between a repair patch and both the substrate concrete and the steel reinforcement [21,22]. However, the interaction between microwave curing and hydration temperatures at early age can have significant effect on the properties and long term deterioration processes in concrete repair patches [23].…”
Section: Introductionmentioning
confidence: 99%